Analysis of factors affecting purchase decision on freshwater ornamental fish (Case Study: Bandung Ornamental Fish Center, Bandung City, West Java) - Farhan, Andre Chandika; Maulina, Ine; Nurhayati, Atikah; Suryana, Asep Agus Handaka (Universitas Malikussaleh, 2024)
Bandung Ornamental Fish Center is one of the freshwater ornamental fish markets in Bandung City. Since its inauguration in 2020, Sentra Ikan Hias Bandung has experienced a decrease in the number of sellers due to the consumer interest on freshwater ornamental fish. This research aims to analyze the consumer characteristics and the factors of consumer behavior and marketing mix (4P) that influence consumer purchasing decisions for freshwater ornamental fish at the Bandung Ornamental Fish Center. This research was conducted from 19 December 2022 to 19 January 2023. The method used in this research is a case study using descriptive analysis for consumer characteristic and statistical inferential methods using PLS-SEM to analyze the factor affecting purchase decision on freshwater ornamental fish. The data collection technique used in this research is a questionnaire and interview. Data analysis in this reaserch uses the PLS-SEM analysis method with a five-point Likert scale using SmartPLS 3 software with nine variables con-sist of personal, psychology, social, culture, price, product, pro-motion, place and purchase decision that listed in Table 1. The analysis results showed that the factors influencing purchase decision of a freshwater ornamental fish at the Bandung Ornamental Fish Center were psychological, social and promotional factors. Researchers suggest the marketers carry out promotions related to consumer psychological and social factors to attract consumer interest.Keywords: Consumer behavior; factor analysis; freshwater ornamental fish; marketing mix; purchase decision; PLS-SEM